Treatment of Trans-Scaphoid Perilunate Injuries of the Wrist using a Nitinol Staple for Fixation - Alec J Talsania; Christine B Novak; Miguel A Pirela-Cruz (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Treatment of trans-scaphoid perilunate injuries of the wrist presents a clinical challenge for patients and the treating hand surgeon. In the past, traditional treatment consisted of combined volar and dorsal approaches, repair of all of the involved ligaments, screw fixation of the scaphoid fracture, and immobilization until the scaphoid is radiographically united. We describe a volar approach that allows for decompression of the carpal tunnel, repair of the rent in the Space of Poirier, and direct internal fixation of the scaphoid fracture with a staple (scaple) that allows for early range of motion. We have used this approach in 18 patients at a Level 1 Trauma Center with satisfactory clinical outcomes.